2012
DOI: 10.2165/11597920-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reactions in Children – International Surveillance and Evaluation (ADVISE)

Abstract: By comparing data from five countries in Europe, Asia and Australia we have shown that the incidence of ADRs in hospitalized children is at least as high as incidences published in adults. However, the variation between countries was mainly due to different populations and treatment strategies. Particular attention should be given to opioid use in hospitalized children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
51
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 37 publications
9
51
2
3
Order By: Relevance
“…Nevertheless, opioid use was more common on paediatric general medical wards in the remaining centres with frequencies between 14.6-21.6%. One reason for this observation could be that the studied patients in UK and AUS were admitted with more painful conditions [16,18]. Other reasons may be greater fear of opioid use, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, opioid use was more common on paediatric general medical wards in the remaining centres with frequencies between 14.6-21.6%. One reason for this observation could be that the studied patients in UK and AUS were admitted with more painful conditions [16,18]. Other reasons may be greater fear of opioid use, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The findings presented are derived from a sub-analysis of the ADVISE (Adverse Drug Reactions in Children -International Surveillance and Evaluation) study [16]. ADVISE was a prospective, multicentre, observational cohort study conducted on five paediatric general medical wards in Australia (AUS), Germany (GER), Hong Kong (HK), Malaysia ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In 2012, an international evaluation of adverse drug reactions (ADRs) among children aged 0 to 18 years revealed that approximately 20% of all ADRs were attributable to cough and cold preparations containing analgesics or opioids. 3 Within the past several years, an increasing number of case reports have illustrated clinically important respiratory depression and even death among infants and children receiving opioids for pain control particularly following tonsillectomy and adenoidectomy (T&A). In 2007, a previously healthy 29-month-old patient received acetaminophen and codeine after tonsillectomy and on post-op day 2, experienced severe apnea and subsequent brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] These infusions require complex dose calculations, multiple manipulations and complicated administration rate adjustments. The project aimed to minimise the risk of medication errors in nurse-or patient-controlled analgesia (N/PCA) for children.…”
mentioning
confidence: 99%